2014
DOI: 10.1186/alzrt256
|View full text |Cite
|
Sign up to set email alerts
|

A coimmunization vaccine of Aβ42 ameliorates cognitive deficits without brain inflammation in an Alzheimer’s disease model

Abstract: IntroductionVaccination against amyloid-β protein (Aβ42) induces high levels of antibody, making it a promising strategy for treating Alzheimer’s disease (AD). One drawback in the past was that clinical trial approval was withheld because of speculation that the Aβ42 vaccine induces CD4+ T cell infiltrations into the central nervous system. To reduce T-cell activation while concomitantly maintaining high anti-Aβ42 titers is a great challenge in immunology.MethodsWe aimed to demonstrate that coimmunization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Notably, our EAE/AD model exhibited considerable neuroinflammation following Aβ immunization, even without myelin basic protein induction. This suggests that Aβ, acting as a self‐protein, can induce autoimmune reactions in EAE/AD mice, which is consistent with previous reports (Marchese et al, 2014; Sardi et al, 2011; Wang et al, 2014). In contrast, AOE1 immunization did not promote neuroinflammation or detrimental immune responses.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, our EAE/AD model exhibited considerable neuroinflammation following Aβ immunization, even without myelin basic protein induction. This suggests that Aβ, acting as a self‐protein, can induce autoimmune reactions in EAE/AD mice, which is consistent with previous reports (Marchese et al, 2014; Sardi et al, 2011; Wang et al, 2014). In contrast, AOE1 immunization did not promote neuroinflammation or detrimental immune responses.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, co-immunization reduced the production of inflammatory cytokine IFN-γ and increased the production of IL-4 in CD4 + T cells, suggesting that an anti-inflammatory effect was induced in the co-immunized mice. Likewise, Wang et al recently reported that co-immunization with Aβ42 peptide and Aβ42-coding DNA ameliorated AD pathology while inhibiting Aβ42-specific T-cell-mediated inflammatory reactions in mice 43 , further supporting the feasibility of this approach. Moreover, the lack of adjuvant use with our combined vaccine is another advantage which can reduce potential side effects associated with strong adjuvants as reported in the AN-1792 and ACC-001 trials.…”
Section: Discussionmentioning
confidence: 82%
“…Another study by Wang and coworkers [32] demonstrated the efficiency of coimmunization with A42 and a plasmid expressing A42. They immunized APP 695 mice intramuscularly with a mixture of A42 and pVAX1-A42 which could express A42.…”
Section: New Methods Of Vaccinationmentioning
confidence: 97%